A construção de um patrimônio cultural: o tombamento federal de Cataguases, Minas Gerais - Paulo Herique Alonso (2010)
Cataguases in Minas Gerais State is a city which stood out for its cultural events in the 20th century: the period of Humberto Mauro cinema and the literature of the Modernist Group Verde, in the 1920s; the modernist architecture with furniture, landscaping, applied arts and the artistical collection from 1940s, great part of the founders of the modern vanguard of architects and artists who acted in Rio de Janeiro. In 1994, IPHAN, the Institute of National Historical and Artistical Heritage recognized the value of such events and put the city under the governmental trusting by establishing a polygonal of preservation in the historical center and the inclusion of sixteen buildings put individually under the governmental trusting. This dissertationinvestigates the way IPHAN managed to make the heritage of Cataguases nationally recognized, as the actions to implement such a recognition and how it has been acting on the preservation of the heritage of the city. It is approached the governmental trusting of Cataguases, the concepts which it was based on, the choiceof some areas and buildings put or not under the governmental trusting and other issues in such a process. One of the main interests in this theme is the fact that this is a protection of urban sets diferently made by the previous IPHAN. The first contacts between the city and IPHAN, in 1987, the process of governmental trusting itself in 1994 until its registering in the official documents only in 2003, until 2009 and the importance iven to the issues related to the managing of this patrimony are also.